Student Languages In Discussion Text In Vocational School (SMK) - Depitaria Br Barus; Erikson Saragih; Rosliani (CV. AFDIFAL MAJU BERKAH, 2022)
Discussion activities can be an effort to improve students' speaking skills in expressing opinions, ideas in discussion. Discussions at school can run well if you stick to the rules of speaking in the principle of politeness. The principle of politeness consists of six maxims, namely the maxim of wisdom, the maxim of humility, the maxim of praise, the maxim of generosity, the maxim of agreement, the maxim of sympathy. This study aims to find and describe the principles of politeness used by students when learning is taking place as well as interactions among students and the implications of politeness principles at school. The data source of this research is the conversations between students in discussions and with teachers at SMK. By using the Leech politeness theory. Data collection techniques using recording and transcription techniques. The type of research used is descriptive method with a qualitative approach. The subjects of this study were students of class XI SMK in Indonesian subjects. The results of this study indicate that there is a violation of the politeness principle, namely 66 utterances and there are also 75 obedience to the politeness principle. The implication for learning Indonesian, namely the principle of politeness is the main requirement to be polite in speaking. The contribution to the school by applying the principle of politeness to all subjects can shape the character of students in speaking skills.